2009
DOI: 10.3390/molecules14082717
|View full text |Cite
|
Sign up to set email alerts
|

Headspace, Volatile and Semi-Volatile Organic Compounds Diversity and Radical Scavenging Activity of Ultrasonic Solvent Extracts from Amorpha fruticosa Honey Samples

Abstract: Volatile organic compounds of Amorpha fruticosa honey samples were isolated by headspace solid-phase microextraction (HS-SPME) and ultrasonic solvent extraction (USE), followed by gas chromatography and mass spectrometry analyses (GC, GC-MS), in order to obtain complementary data for overall characterization of the honey aroma. The headspace of the honey was dominated by 2-phenylethanol (38.3–58.4%), while other major compounds were trans- and cis-linalool oxides, benzaldehyde and benzyl alcohol. 2‑Phenylethan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0
6

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 25 publications
1
33
0
6
Order By: Relevance
“…Indeed it is perhaps to soon postulate biological origins and roles for these VOC's as part of a stress-sensitive response in breath. At this stage it is helpful to note that benzaldehyde is a common food component and occurs naturally in fruits like apples and honey [31,30] likewise terpenes occur naturally in foodstuffs, [29]. These components may be due to dietary intake and may not have an endogenous origin.…”
Section: Multi-variate Analysismentioning
confidence: 99%
“…Indeed it is perhaps to soon postulate biological origins and roles for these VOC's as part of a stress-sensitive response in breath. At this stage it is helpful to note that benzaldehyde is a common food component and occurs naturally in fruits like apples and honey [31,30] likewise terpenes occur naturally in foodstuffs, [29]. These components may be due to dietary intake and may not have an endogenous origin.…”
Section: Multi-variate Analysismentioning
confidence: 99%
“…The fibre was conditioned prior to use according to the manufacturer instructions by inserting into the GC injector port. Procedure of the HS-SPME was described in [11] [29]. A total of 5 ml of honey/H 2 O soln.…”
Section: Experimental Partmentioning
confidence: 99%
“…USE was performed in an ultrasound cleaning bath (Transsonic Typ 310/H, Germany) by the mode of indirect sonication, at the frequency of 35 kHz at 25 AE 38 as described in [11] [29]. Forty grams of Salix spp.…”
Section: Experimental Partmentioning
confidence: 99%
“…However, none of the single methods proposed proved to be simple, rapid, and objective. Recently, our research group suggested a two-way approach for the isolation of the honey volatile compounds, i.e., headspace solid-phase microextraction (HS-SPME) and ultrasonic solvent extraction (USE) [7] [8]. With this approach, it was possible to obtain a more detailed insight into the honey volatile and semi-volatile compounds and to minimize the risks of compound discrimination due to their partial extraction.…”
mentioning
confidence: 99%